OPTIMALISASI PERTANIAN BERKELANJUTAN MELALUI INTEGRASI MATEMATIKA, AGROTEKNOLOGI DAN LITERASI EKONOMI UNTUK PEMBERDAYAAN MASYARAKAT LABUHANBATU - Irmayanti; Badrul Ainy Dalimunthe; Tetty Rahmiati Harahap; Yusmaidar Sepriani; Erni Wahyuni; Izmawal Pebriani Nasution (JURNAL BIMA, 2025)
The "Makmur Sejahtera" Farmers Group in Labuhanbatu faces low productivity due to the limited adoption of agrotechnology, mathematical literacy, and economic understanding in managing their farms. This topic is important because the integration of technology, applied mathematics, and economic empowerment can increase farmer efficiency and income, supporting sustainable food security. The objective of this community service is to empower 45 partner farmers through training in the application of agrotechnology (drip irrigation and soil sensors), simple mathematical modeling (for yield prediction and cost calculation), and economic literacy and agricultural product marketing. The methods used include needs identification, workshops, field practice, and pre-test-post-test evaluations. The results show a 78% increase in hard skills in agrotechnology management and a 65% increase in soft skills such as cooperation and self-confidence. On average, farmers' income increased by 20% thanks to production efficiency and business diversification. In conclusion, this community service effectively strengthens farmers' technical and economic capacity, creating a replicable model of sustainable agriculture to support the welfare of rural communities.